2015
DOI: 10.1002/pon.3750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pillars4life: a virtual coping skills program for cancer survivors

Abstract: Objective Pillars4Life is an educational program that teaches coping skills to cancer patients in a virtual group setting; it was recently implemented at 17 hospitals across the USA. The cost-effective, scalable, and assessable Pillars4Life curriculum targets psychosocial resources (e.g., self-efficacy and coping skills) as a means to reduce symptoms (e.g., depression, anxiety, and posttraumatic stress) and enhance quality of life. Methods Cancer patients were recruited from hospitals that received the LIVES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
(29 reference statements)
1
9
0
3
Order By: Relevance
“…High attrition rates are major reasons for reduced effect sizes of online interventions compared with face-to-face treatments [72]. Our attrition rate of 32% is consistent with other oncology online studies that include one for fatigue that had a 38% dropout and another for coping skills in cancer survivors that had a 32% attrition rate [29, 73]. It is also worth noting that a meta-analysis of dropouts from in-person psychotherapy for anxiety is 17%, with no definable modifiers based on patient, therapist, or treatment variables and can range up to at least 38% for some in-person treatments [74, 75].…”
Section: Discussionsupporting
confidence: 81%
“…High attrition rates are major reasons for reduced effect sizes of online interventions compared with face-to-face treatments [72]. Our attrition rate of 32% is consistent with other oncology online studies that include one for fatigue that had a 38% dropout and another for coping skills in cancer survivors that had a 32% attrition rate [29, 73]. It is also worth noting that a meta-analysis of dropouts from in-person psychotherapy for anxiety is 17%, with no definable modifiers based on patient, therapist, or treatment variables and can range up to at least 38% for some in-person treatments [74, 75].…”
Section: Discussionsupporting
confidence: 81%
“…A cross‐sectional survey on association between mental health and communication among families of breast cancer survivors found that open and productive communication among breast cancer survivors and their families was associated with better mental health . The only other report we found on a coping skills program focusing on self‐efficacy and control that assessed the impact on QoL is the Pilars4life program ; this program involved virtual meetings with a certified instructor weekly over a 10 week period. At 3‐ and 6‐month follow‐up, mean scores improved on measures of depression (Patient Health Questionnaire), anxiety (Generalized Anxiety Disorder), posttraumatic stress (Posttraumatic Stress Disorder Checklist), fatigue (Functional Assessment of Chronic Illness Therapy‐Fatigue), and well‐being (FACT‐General) from baseline (all p < 0.01).…”
Section: Discussionmentioning
confidence: 94%
“…Estes autores afirmam ainda que a educação e a informação são essenciais para reduzir os níveis de ansiedade, uma vez que geralmente os medos se baseiam em informações incorretas. Smith et al (2015) desenvolveram um programa com vista ao ensino e treino de habilidades de coping para os sobreviventes de cancro e concluíram que a participação no programa foi associada a melhorias estatísticas e clinicamente significativas, quer para a redução da ansiedade, depressão, stress pós-traumático e fadiga, quer para o aumento do bem-estar. Também Towsley et al (2007) exploraram as experiências de coping durante o processo de transição para a sobrevivência do adulto com cancro e desenvolveram um modelo denominado Learning to live with it, demonstrando como os sobreviventes recorrem a várias estratégias, atitudes e experiências de vida anterior para integrar a doença oncológica nas suas vidas.…”
Section: Discussionunclassified